Kaji Pembuatan Sistem Kontrol Mesin Vacuum Evaporator Penurun Kadar Air Madu Kapasitas 50 Liter - Angga Islam Darmawan; Nazaruddin Nazaruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Honey is a food that is very beneficial for health. Based on SNI 01-3545-2004 standards for foodstuffs honey, determined the content of water is allowed a maximum of 22% and capped at a maximum processing temperature at 40oC so that other content in honey is not damaged. Evaporating the water at low temperatures can be done by the method of vacuum systems. By lowering the pressure below 1 atm or in accordance with the graph of temperature versus pressure, where to evaporate water at a temperature of 40oC, the pressure required is 7,4 kPa. Vacuum evaporator machine is a machine that serves as a food processing machine that can remove water content contained in the meal ingredients. This study makes a planning vacuum evaporator engine control system for controlling the process. The temperature at 40oC honey processing predefined SNI can be achieved by creating a temperature control system with a controller and use of sensors, so that the temperature treatment process is maintained to keep the content contained in the honey. Pressure is used to evaporate water at a temperature of 40oC is under a pressure of 1 atm, of 7,4 kPa. To achieve the required pressure compressor engine 1 vacuum. The control system using a vacuum compressor control systems that perform manual where the feedback is done by humans. In the processing of round screw mixer and serve as a tool to stir the honey during processing so that warming of honey evenly. With the processing time variation, obtained honey with moisture content of 20.6% at the variation time of 4 hours, the water content of 19.8% at 8 hours and time variations in the time variations are also available 12 hours a moisture content of 19.6%. In accordance with SNI standards 01-3545-2004 of maximum water content of 22% honey can already be obtained by variation of the processing time of 4 hours.Keywords: control systems, vacuum evaporator, honey